Design and Analysis of Clinical Nursing Research Studies - Martin, Colin R.; Thompson, David R. (Routledge Essentials for Nurses, 2000)
This invaluable text on the design and analysis of clinical research studies explains the basis of experimental design and statistics in a way that is sensitive to the clinical context in which nurses work. It uses data from actual studies to illustrate how to:*design the study*use and select data*present research findings*use a computer for statistical analysis.The scope of the study designs and associated statistical techniques covered in the book allow both the beginning nurse researcher and the more seasoned professional nurse investigator to approach a research study with confidence and optimism. The authors show how qualitative data can be approached quantitatively, what the advantages of this are from the nursing viewpoint, and how quantitative methodology can help nurses to develop a common research language with other disciplines involved in patient care.